2021
DOI: 10.2196/25847
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on Digital Mental Health Interventions for Adolescents and Young People: Systematic Overview

Abstract: Background An estimated 1 in 5 adolescents experience a mental health disorder each year; yet because of barriers to accessing and seeking care, most remain undiagnosed and untreated. Furthermore, the early emergence of psychopathology contributes to a lifelong course of challenges across a broad set of functional domains, so addressing this early in the life course is essential. With increasing digital connectivity, including in low- and middle-income countries, digital health technologies are con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
146
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(153 citation statements)
references
References 50 publications
3
146
0
4
Order By: Relevance
“…A systematic overview of meta-analyses and systematic reviews found digital mental health interventions for young people have reasonably positive effects [79]. The evidence of effectiveness was mostly found on anxiety and depression, and to a lesser extent on stress-the main concerns are evidence-based treatment content or in-person elements that may improve engagement [79].…”
Section: Digital Mental Health For Young Peoplementioning
confidence: 99%
See 2 more Smart Citations
“…A systematic overview of meta-analyses and systematic reviews found digital mental health interventions for young people have reasonably positive effects [79]. The evidence of effectiveness was mostly found on anxiety and depression, and to a lesser extent on stress-the main concerns are evidence-based treatment content or in-person elements that may improve engagement [79].…”
Section: Digital Mental Health For Young Peoplementioning
confidence: 99%
“…A systematic overview of meta-analyses and systematic reviews found digital mental health interventions for young people have reasonably positive effects [79]. The evidence of effectiveness was mostly found on anxiety and depression, and to a lesser extent on stress-the main concerns are evidence-based treatment content or in-person elements that may improve engagement [79]. Only a small proportion of digital platforms are evidence-based-more needs to be known about the (cost-)effectiveness of the type of service provided, target subpopulation, and the current standard of care [79].…”
Section: Digital Mental Health For Young Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, reviews of digital mental health interventions consistently raise concerns about the accessibility of digital technologies among disadvantaged groups [ 11 ] and difficulties keeping users engaged even among groups with access to technology [ 12 ]. Though promising gamified approaches have recently emerged [ 12 , 13 ], evidence from low-resource settings is especially scare [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on cCBT interventions have been conducted predominantly in high-income countries (Lehtimaki et al, 2021), but see (Martínez et al, 2018) for depression and (Fu et al, 2020) for all mental health disorders in LMICs. A recent meta-analysis reported that 92% of the studies on diagnosed depression had been conducted in Western Europe, North America, or Australia (Köhnen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%